Traffic accident application using Geographic Information System. - Lim, Yu Liang; Law , Teik Hua; Ma'soem, Dadang Mohamad (2005)
Many highway agencies have been using Geographic Information System (GIS) for analyzing accident data. Identification of problematic locations is one of the most important aspects in accident studies. The GIS based application combines the information collection capabilities with the visualization. The GIS and Road Accident View System are a set of applications developed for managing accident database entries. The developed system wasdesigned based on the Universiti Putra Malaysia (UPM) community area and may be adapted very easily to any other places. The system was developed using Microsoft Visual Basic 6.0 in Windows XP platform. The database was designed in term of textual format. The Accident Report from UPM security unit used as the source for information needed in the database development. The location of the accident was recorded on a map. And by indication on it, the user can perform queries on a particular condition to get the number of accidents.